(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aims to shed light on the lean management method and its role in reducing waste in its various forms and to show the extent of application of this method in industrial companies. ) in reducing supply chain risks before, during and after their occurrence and demonstrating the role of agile management in the sustainability of supply chains. The researcher relied on the descriptive analytical approach. In the theoretical section of the research, the concept of lean management, its principles and objectives were studied, the concept of supply chain and the concept of supply chain risks and types of these risks were studied. In the practical section, a questionnaire was designed that included a set of statements related to the topic of research and appropriate statistical methods were used depending on The program (SPSS23) in analyzing data and testing hypotheses, the research community is represented by the administrative cadres in the industrial companies in the industrial city in Hasya, where an intentional sample of the administrative cadres in the industrial companies in Hasya was selected, where the size of the research sample was (64) individuals The study reached a (positive) significant relationship between lean management dimensions (organizing work site, continuous improvement, standard work, multi -functional workers, six Sigma) and reducing supply chain risks before it occurs. And a (positive) significant relationship between lean management dimensions (organizing work site, continuous improvement, standard work, multi -functional workers, six soms) and between reducing supply chain risks during its occurrence. And a (positive) significant relationship between lean management dimensions (organizing work site, continuous improvement, standard work, multi -functional workers, six Sigma) and between reducing supply chain risks after its occurrence.